Pembuatan Peta Blok RT Desa Bingkulu Kecamatan Tambang Ulang - Inayah, Nurul; Sobatnu, Ferry; Irawan, Faris Ade; Sari, Dewi Nur Indah (Jurnal IMPACT: Implementation and Action, 2018)
ABSTRACT Geodetic science is practically making maps of the earth's surface. Bingkulu village currently has problems with the absence of a village map for village government officials and local residents. The absence of this village map made difficulties for village and community equipment to find out information on Neighborhood Association boundaries and land use in the Bingkulu Village area at Tambang Ulang District. To make a map of the Neighborhood Association boundaries, using survey method with a GPS handheld equipment and identifies the Neighborhood Association boundaries according to the direction from the village officials who is very familiar with the conditions in the field. Making Neighborhood Association boundary maps is done through digitizing in the QGIS application by displaying corrected satellite images. Through the QGIS application, digitization is carried out in accordance with the conditions in the research location, by paying attention to the appearance of the earth in the satellite image of Bingkulu Village. The objects digitized in this process are roads, Neighborhood Association boundaries, village boundaries, public facilities. Furthermore the interpretations did and the result is that land use in Bingkulu Village includes plantations, rice fields, and built land. The Plantations distributed in almost the Bingkulu region with two types of commodities, namely oil palm and rubber trees. In addition, land use in all Bingkulu region is dominated by oil palm plantations. So that oil palm trees are still the main commodity of plantations in Bingkulu Village. Keywords: survey, satellite image, boundary, village